Religious Deradicalization, Inclusivism and Multiculturalism: A Critical Analysis of Islamic Boarding School Education in the United States - Ali Mufron (Yayasan Adra Karima Hubbi, 2026)
Background. Religious radicalism in the United States poses a significant challenge in a multicultural society, where diverse religious and cultural identities coexist. Radical interpretations of religious teachings can lead to intolerance and threaten social cohesion. Purpose. This study examines the role of education and interfaith engagement in preventing religious radicalism and promoting tolerance. Method. A qualitative approach was employed using literature analysis and conceptual review of deradicalization programs. Data were collected from academic publications, policy documents, and reports related to religious education, multiculturalism, and interfaith dialogue in the United States. Results. The findings show that inclusive education and interfaith communication effectively reduce radical narratives and strengthen mutual understanding. Educational institutions, including Islamic boarding schools and community-based organizations, have implemented models that emphasize dialogue, cultural awareness, and respect for diversity. Conclusion. Educational collaboration and multifaith engagement are key strategies for preventing radicalism and strengthening social cohesion. As a practical contribution, this study supports the development of multifaith education programs that promote tolerance and cultural awareness among educators, students, and the wider community.